Combined photoemission and scanning tunneling microscopy study of the surface-assisted ullmann coupling reaction - Chen, Min; Xiao, Jie; Steinrück, Hans-Peter; Wang, Shiyong; Wang, Weihua; Lin, Nian; Hieringer, Wolfgang; Gottfried, J. Michael (Journal of Physical Chemistry C, 2014)
The adsorption and reaction of 4,4-dibromo-para-terphenyl (DBTP) and 1,3,5-tris(4-bromophenyl)benzene (TBB) on Cu(111) surface were studied with X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), and density functional theory (DFT) calculations. In addition, complementary scanning tunneling microscopy (STM) data are presented. At submonolayer coverage, scission of C-Br bonds occurs between 170 and 240 K. The estimated activation energy for this process is considerably lower than the C-Br bond energy, indicating that bond scission is assisted by Cu atoms of the substrate. The remaining molecular backbones undergo linkage by C-Cu-C bonds to form organometallic oligomers. Annealing of these oligomers leads to the formation of C-C bonded covalent two-dimensional networks. Above monolayer coverage, complete C-Br cleavage requires higher temperature, confirming the role of the Cu surface in the reaction. The results provide insight into the C-Br bond scission as the initial step of the surface-assisted Ullmann reaction. © 2014 American Chemical Society.